Perception of the Trome Newspaper in public transportation drivers in the City of Lima, Perú - Chávez Espinoza, Evelyn Lizeth (2020)
The study aims to relate the perception to the form and content of the newspaper Trome by the type of public transport drivers of Metropolitan Lima. Therefore, a survey of 25 Likert-type scale design items with validity and reliability of .896 was used in 153 drivers of the regular transport mode and 83 of the Metropolitan Lima taxi prior to consent. The results show that there is an association between the dichotomy content and form of the journalistic message with the type of public transport driver. Thus, regular transport drivers have a greater relationship to the message through the form focusing on the colors, images and eye-catching headlines, stop paying attention to background issues because - as they say - they are convinced of the truth of the newspaper Trome. Instead, the taxi driver is also associated with the content of the message, but in a minimal proportion. In general terms, both groups do not notice implicit messages with ease, so it is concluded that the great influence of the newspaper is given by the form, since a limited sector of carriers is aware of the implicit message.